Gambaran Hemodinamik Pre Dan Pasca Anastesi Spinal Pada Pasien Sectio Ceasarea - Anggrayani, Ayudarni; Susanto , Amin; M Sebayang , Septian; Burhan , Asmat (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Spinal anesthesia is a widely used regional anesthetic technique for cesarean section procedures due to its rapid onset, effectiveness, and safety. However, spinal anesthesia carries a significant risk of hemodynamic changes, such as hypotension and alterations in heart rate, which may affect both maternal and fetal conditions. This study aims to describe the hemodynamic profile before and after spinal anesthesia in cesarean section patients in the operating room of Muhammadiyah Hospital Palembang. This research employed an analytical observational design with a cross-sectional approach. A total of 60 patients undergoing cesarean section with spinal anesthesia were selected using total sampling. Data were collected through observation of blood pressure, mean arterial pressure (MAP), heart rate, and respiratory rate before anesthesia and at the 5th, 20th, 35th, and 50th minutes after the procedure. The results showed that 41.7% of respondents experienced hypotension at the 5th minute, 36.7% had MAP values below 60 mmHg, and 25% developed compensatory tachycardia. Hemodynamic parameters began to stabilize between the 35th and 50th minutes. This study concludes that significant hemodynamic changes occur after spinal anesthesia, especially in the early phase. Therefore, close monitoring of the patient’s hemodynamic status is essential to prevent further complications.